2017
DOI: 10.1186/s12868-017-0357-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of escitalopram and paroxetine on mTORC1 signaling in the rat hippocampus under chronic restraint stress

Abstract: BackgroundRecent studies have suggested that the activation of mammalian target of rapamycin (mTOR) signaling may be related to antidepressant action. Therefore, the present study evaluated whether antidepressant drugs would exert differential effects on mTOR signaling in the rat hippocampus under conditions of chronic restraint stress. Male Sprague–Dawley rats were subjected to restraint stress for 6 h/days for 21 days with either escitalopram (10 mg/kg) or paroxetine (10 mg/kg) administered after the chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 62 publications
2
12
0
2
Order By: Relevance
“…In the present study, DEX treatment decreased the BDNF level, total dendritic outgrowth, and spine density of primary hippocampal cells of rats, and both LY341495 and ketamine treatment dose-dependently reversed these effects, confirming that LY341495 affects BDNF level, dendritic outgrowth, and spine density. Our results are similar to those of previous studies 38,49,50 . Zanos et al reported that the ketamine metabolite (2R,6R)-hydroxynorketamine-(2R,6R)-HNK acts on mGlu2 receptor and that combined sub-effective doses of the mGlu 2/3 receptor antagonist LY341495 and (2R,6R)-HNK have synergistic effects on gamma oscillations and antidepressant-relevant behavioral actions 51 .…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, DEX treatment decreased the BDNF level, total dendritic outgrowth, and spine density of primary hippocampal cells of rats, and both LY341495 and ketamine treatment dose-dependently reversed these effects, confirming that LY341495 affects BDNF level, dendritic outgrowth, and spine density. Our results are similar to those of previous studies 38,49,50 . Zanos et al reported that the ketamine metabolite (2R,6R)-hydroxynorketamine-(2R,6R)-HNK acts on mGlu2 receptor and that combined sub-effective doses of the mGlu 2/3 receptor antagonist LY341495 and (2R,6R)-HNK have synergistic effects on gamma oscillations and antidepressant-relevant behavioral actions 51 .…”
Section: Discussionsupporting
confidence: 93%
“…12 rats in each group were used for behavioral experiments, and the remaining 18 were used for subsequent experiments. The chronic restraint stress procedure was performed between 9:00 and 15:00, as previously described (Zhao et al, 2013; Seo et al, 2017). Briefly, except rats in C group, all rats were daily restrained into a transparent plexiglass tube (26 cm long and 8 cm in diameter) for 6 h over 21 consecutive days (Figures 1A,B).…”
Section: Methodsmentioning
confidence: 99%
“…Concerning the signaling pathways involved in the effects of cannabinoid drugs in stress-related neuroplasticity, the mechanistic (or mammalian) target of rapamycin (mTOR) protein has been implicated in synaptogenesis, proliferative processes, and synaptic strength modulation (Li et al, 2010 ; Ma et al, 2010 ; Romine et al, 2015 ; Liang et al, 2016 ). Some studies showed that different paradigms of stress exposure reduce mTOR activity (Iiu et al, 2016 ; Xia et al, 2016 ; Zhuang et al, 2016 ; Seo et al, 2017 ), and cannabinoid drugs can interfere with this signaling pathway (Puighermanal et al, 2009 ; Palazuelos et al, 2012 ; Gobira et al, 2015 ; Giacoppo et al, 2017 ). For example, Zhong et al ( 2014 ) demonstrated that the antidepressant-like responses trigged by JZL184, an inhibitor of 2-AG hydrolysis, in chronically stressed mice were dependent on mTOR signaling.…”
Section: Stress Induces Changes In Cannabinoid-mediated Hippocampal Nmentioning
confidence: 99%